Determinan Kepatuhan Penerapan Standar Operasional Prosedur (SOP) Dalam Penerimaan Karet di PT. Sampit International Banjarmasin Tahun 2015 - Khairul Anam (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2016)
SOP is a simple instruction to complete a routine task which is the most effectiveway to meet the operational requirements. According to the data from the ILO, everyyear in the world happens 270 million accidents at work, workers suffer 160 milliondiseases because of work, 2.2 million deaths and finance of 1.25 trillion USD. InIndonesia, in the period of 2009, there were 22.338 cases of the total 96.314 cases in 2009for accidents at work at the age of 26 -30 years.The purpose of this study is to investigatethe obedience determinants of the implementation of Standard Operating Procedures(SOP) on rubber admission in Sampit International Company Banjarmasin in 2015.Thisresearch is a type of analytical research which uses a Cross Sectional approach usingprimary data. The total sample of this research is 100 respondents, which uses a samplingtechnique that is saturated by making the entire population as a sample. Data wereanalyzed in univariate way, bivariate way using Chi Square statistic test.The researchshows that 1 between 5 respondents are less adherent to the implementation of SOP. Thevariables which are related are the level of education, work experience (the employmentperiod), knowledge, regulation, and supervision. in the other hand.